Dampak Kenaikan Harga Bahan Bakar Minyak Terhadap Elastisitas Permintaan Sembako di Pasar Segiri Kota Samarinda - Arwin Arwin; Sutrisno Sutrisno; Nurfitriani Nurfitriani (Journal of Business and Economics Research (JBE), 2023)
The increase in fuel prices was influenced by external factors, namely the increase in world oil prices as a result conflict between Ukraine and Russia. The increase in the price of fuel oil (BBM) will certainly cause panic for the community because it will have an impact on increasing prices for businesses such as the clothing sector, food and so on. The increase in fuel prices in Indonesia is seen as capable of influencing purchasing power declining society. The increase in the price of basic foodstuffs will affect consumer response make purchasing decisions at the Segiri Market, Samarinda City. The purpose of this research is to find out. the impact of the increase in fuel prices on the elasticity of demand for groceries at Segiri Market, Samarinda City. This research is a descriptive qualitative research and the nature of this research is a field research. Data collected in research This is primary data by conducting observations and interviews. The data collected is then calculated and interpreted to draw conclusions. The increase in the price of BM fuel has no impact on the elasticity of demand for groceries at Segeri Market, Samarinda City. The provisions are Rice, Cooking oil, sugar, salt, milk, eggs, beef, vegetables, onions (perfectly inelastic or ED = 0). Chicken and chili (in elastic or ED <1). The consumers of Segiri Market, Samarinda City are still willing buy goods according to needs even though there is an increase in fuel prices because basic food is a necessity essential for daily needs.